Status Sosial Ekonomi Orang tua Menentukan Terhadap Hasil Belajar Ekonomi Mikro - Andini, Andini; Khusaini, Khusaini; Syamiya, Estu Niana (Universitas Hamzanwadi, 2024)
This research aims to analyze the influence of parents' socio-economic status on microeconomics learning outcomes. The sample in this study was 310 students of the economics education study program, accounting study program and management study program at Syekh-Yusuf Islamic University using a simple random sampling technique. The data collection technique used is questionnaire data. Meanwhile, the analysis method uses Weight Least Square (WLS). The results of the research show that parents' socio-economic status influences microeconomics learning outcomes and the next variable, namely gender, influence and significant in microeconomics learning outcomes.